2005
DOI: 10.1055/s-2005-865290
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Synthesis and Chemical Properties of 3-Acylamino-6-poly­fluoroalkyl-2H-pyran-2-ones

Abstract: A number of 3-acylamino-6-polyfluoroalkyl-2H-pyran-2-ones 3 were synthesized from b-alkoxyvinyl polyfluoroalkyl ketones 1 and N-acylglycines 2 in acetic anhydride in high yield. The reactions of trifluoromethyl-containing 2H-pyran-2-one 3b with Oand N-nucleophiles were studied and 3-N-benzoylamino-6-hydroxy-6-trifluoromethyl-5,6-dihydro-2H-pyran-2-one (13), 3-Nbenzoylamino-6-hydroxy-6-trifluoromethyl-5,6-dihydro-2H-pyridin-2-one (14a), and N-and O-substituted 3-(N-benzoylamino)-6-trifluoromethyl-2H-pyridin-2-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 13 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…Consequently, the major products were compounds 6c and 7c, identical to the products obtained from pyrone 3c. Compounds 2c and 10 [9] ( Figure 2) were also isolated from the reaction mixture as by-products in 20 % and 6 % yields, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, the major products were compounds 6c and 7c, identical to the products obtained from pyrone 3c. Compounds 2c and 10 [9] ( Figure 2) were also isolated from the reaction mixture as by-products in 20 % and 6 % yields, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…We have previously reported the synthesis [9] and reactivities [9,10] of pyrones 3, which in this paper have served as convenient precursors of the target amino acids 1 and 2. The pyrones 3 have the same carbon skeletons and necessary functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…The X- ray analysis proved that the benzamido group and the oxygen atom were attached in an ortho relationship, and that the H 15 and H 16 protons have a cis configuration (Figure 3). Some chemical transformations with p-(trifluoromethyl) anilides 5a, 5f and 5g have also been investigated.…”
Section: Resultsmentioning
confidence: 98%
“…We found that the heating of pyrone 1a [16] with α-fluorostyrene (2) [9] in toluene gave only one of the possible regioisomeric products, the phenyl-substituted N-benzoyl-4-(trifluoromethyl)aniline 5a in a very slow reaction (toluene, sealed tube, 120°C, 34 d, 43 % yield, 32 % of pyrone 1a was recovered) (Scheme 1). Interestingly, the reaction of β-fluorostyrenes 7 [17] with pyrone 1a gave the same product in Scheme 1. 54 % yield after 40 d at 120°C (34 % of pyrone 1a was recovered).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation